Implementation of the Odoo Point of Sale ERP Module at Gordio Store - Niko Putra Prawiratama Wijanarko; Syaifudin Abdullah; Teddy Siswanto (Intelmatics, 2021)
Gordio Store is a UMKM that is engaged in developing clothing convection in Tanah Abang Market, Central Jakarta. Operational business processes This business is still done manually and not yet computerized, so the transfer of information about sales is done manually.The ongoing sales business process at Gordio Store has become inefficient and the owner has experienced some difficulties, especially information on sales and sales transactions last week or month.Therefore, it is necessary to apply Enterprise Resource Planning (ERP) technology with the aim of resolving these problems. The selection of software used is Odoo software, because it is considered open source and is easy to use and can also keep pace with changes and is integrated as a whole to meet the company's most complex operational needs. From the implementation results show that the Odoo application can overcome the problem of sales data information using the Point of Sale module in Gordio Store. It is expected that with this ERP system business operations can be more effective and efficient so that it is expected to provide more benefits for business owners.